The application of assisted reproductive technologies for the production of Cape Buffalo(Syncerus caffer) embryos - Kidson, Annadie (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1998.